An analytical investigation into the use of magneto-rheological elastomers to suppress flexural waves in beams. (2017) - Almeida, F.C.L.; Brennan, M.J.; Paschoalini, A.T.; Santos, V.M.; Bellucci, F.S.; Job, A.E.
Abstract: Magneto-rheological elastomers (MRE) are materials that change their stiffness and damping properties when subject to a magnetic field. They have evolved from magneto-rheological fluids which have some disadvantages, in that the particles in the fluid tend to collect as sediment. This means that the fluids require agitation to prevent this. MREs are a new material, so not much work has been carried out on their use to control vibration in mechanical structures. This paper investigates the effectiveness of MREs to control wave motion in a one-dimensional structure. A model of an MRE, coupled to a beam, is developed so that simulations can be conducted to demonstrate the effectiveness of MRE as a wave control measure. It is shown that the MRE can be used to control the amplitudes of the reflected and transmitted waves from the section of beam containing the MRE.